Understanding Gender and Inclusive Governance: An Explorative Overview - Kumije, David; Emmanuel, Adejoh; Achimugu, Ikani; Agbaji, Hannah E.; Odiba, Shaibu (Kashere Journal of Politics and International Relations, 2025)
Building inclusive nations, states and societies is widely understood as a central concern for international development, and history has shown that inclusive nations, states and societies are more prosperous, effective and resilient in the long run. Gender and governance is about finding the conditions under which public affairs are managed so that women are included equally in the government, so that gender equality is one of the goals or results of public management. This understanding would have to be finessed considerably so that in terms of the delivery of justice, regulation of the economy, delivery of public services, resolution of social and political conflict, and other business of government, women are equally included and gender equality is maintained as a goal. Thus, getting more women into public office and decision-making positions is an important issue about equal opportunities and ultimately human rights; although it is not a guarantee that it will necessarily produce better quality governance from a gender perspective. Against the foregoing backdrop, this paper is exploring the understanding of gender and inclusive governance. The paper is anchored on the equity theory of leadership which holds the assumption that an individual is motivated by the desire to be equitably treated in his or her work relationship based on fairness. The study adopted a content/document analysis. Based on the findings, it is recommended that although women participation in governance is gradually gaining acceptance even in predominantly male societies, there is need to review upwards constitutionally, the number and percentage for both elective and appointable positions to women.